The Political Geography of Cities - Richard Bluhm; Christian Lessmann; Paul Schaudt (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the link between subnational capital cities and urban development using a global data set of hundreds of first-order administrative and capital city reforms from 1987 until 2018. We show that gaining subnational capital status has a sizable effect on city growth in the medium run. We provide new evidence that the effect of these reforms depends on locational fundamentals, such as market access, and that the effect is greater in countries where urbanization and industrialization occurred later. Consistent with both an influx of public investments and a private response of individuals and firms, we document that urban built-up, population, foreign aid, infrastructure, and foreign direct investment in several sectors increase once cities become subnational capitals.
Keywords: H10; R11; R12; O10; 330; capital cities; administrative reforms; economic geography; urban primacy